Simulation of heterogeneously catalyzed esterification for the production of biodiesel using reactive distillation column - Ahmad Atiqurrahman, Hasan (2009)
Fatty acid esters serve as feedstock for production of cosmetic, detergents, and as a fuel for production of biodiesel. They were produced by the reaction between fatty acids and the alcohols to produced fatty acid ester and water. The reactive distillation column performance for the production of 2-ethylhexyl dodecanoate by esterification of dodecanoic acid with 2-ethylhexanol has been studied in present research. Simulation on esterification process was done in equilibrium stage model using RADFRAC model. Kinetic model and thermodynamic model based on concentration is incorporate into RD equilibrium stage model. The simulation was carried out to determine the effect of the important parameter and design factor such as column operating pressure, reflux ratio, feed location arrangement, height of reactive zone and also the temperature of reactant feed enters to the column. A technically optimized RD process for production of 2-ethylhexyl dodecanoate has been proposed based on the simulated data. As a result, the optimum operating parameters are, reflux ratio at 0.1, temperature of feed enters to the column both are at 303.15 right on the reactive zone at stage five and stage 10, Height of reactive zone is six stages, whereby the operating column pressure is 30kpa in order to have an acid conversion about 99.3%.-Author-